HUBUNGAN KADAR HBA1C DENGAN DERAJAT ULKUS DIABETIK MENURUT KLASIFIKASI MEGGITT-WAGNER PADA PASIEN DIABETES MELITUS TIPE 2 DI RSUD DR. H. ABDUL MOELOEK BANDAR LAMPUNG PERIODE JANUARI-JULI 2022 - Salsabila, Kamila; Kurniati, Intanri; Wulan, Anggraeni Janar; Wintoko, Risal (Medula, 2026)
Type 2 diabetes mellitus can lead to various complications if they are not managed adequately, including diabetic ulcers. Classification of diabetic ulcers is necessary to describe the lesion and to study the prognosis of the patients. The Meggit-Wagner classification was chosen because it is a classification system that has many advantages. Measurement of glycated hemoglobin (HbA1C) is a glycemic control that is considered good for describing blood sugar levels. High blood glucose levels are one of the reasons why patients have difficulty healing wounds, which can affect the grade of diabetic ulcers. The purpose of this study was to determine the relationship between HbA1C levels and the grade of diabetic ulcers according to the Meggitt-Wagner classification in type 2 diabetes mellitus patients at Dr. H. Abdul Moeloek Hospital Bandar Lampung from January-July 2022. This research is a retrospective observational analytic study with a cross-sectional approach. The research sample was 66 patients. The data used is medical records. Selection of the sample using total sampling technique. Statistical analysis was performed using univariate and bivariate analysis. The results of the bivariate analysis using the chi-square test showed a value of p=0.003 (p <0,05) in HbA1C levels and the grade of diabetic ulcers, which means that there is a significant relationship between the variables. There is a significant relationship between HbA1C levels and the grade of diabetic ulcers according to the Meggitt-Wagner classification in type 2 diabetes mellitus patients at Dr. H. Abdul Moeloek Hospital Bandar Lampung from January-July 2022.